Metabolic signatures of performance in elite world tour professional cyclists during competition - Nemkov, T. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Investigations in elite professional athletes offer a unique opportunity to determine the ceiling of human performance, providing a benchmark to compare human physiology of healthy occasional, recreational, semi-professional and professional athletes. While omics characterizations of recreational and professional athletes under controlled acute training regimens have provided information regarding substrate utilization as a function of exertion, studies are scarce on these processes in elite professional athletes during testing in the field and, more importantly, World Tour competitions. METHODS: Using dried blood spot collection to circumvent logistical hurdles associated with field sampling, whole blood samples were isolated from 28 international-level professional male cyclists before and after a graded exercise test (GXT) to volitional exhaustion and before and after a long aerobic field training (FT) session (180 km). Additional samples were taken from 5 of these cyclists before and after three stages of a multi-stage World Tour race. Samples were analyzed using high-throughput mass spectrometry-based metabolomics and lipidomics. RESULTS: Blood profiles of lactate, carboxylic acids, fatty acids and acylcarnitines differed between different exercise modes (GXT and FT). The GXT elicited significant accumulations in lactate and succinate, in addition to significant elevations in free fatty acids and acylcarnitines. Conversely, FT elicited a larger magnitude of increase in fatty acids and acylcarnitines without appreciable increases in lactate or succinate. Comparable signatures were revealed after sprinting and climbing stages, respectively. In addition, signatures of fatty acid oxidation capacity correlated with competitive performance. CONCLUSION: Collectively, these studies provide a unique view of alterations in the blood metabolome of elite athletes during competition and at the peak of their performance capabilities. Furthermore, they demonstrate the utility of dried blood sampling for omics analysis, thereby enabling molecular monitoring of athletic performance in the field during training and competition.